Queer, crip, rights? Establishing a new identity approach to disability for a post- Convention on the Rights of Persons with Disabilities World - Watson, Danielle Abigail Madeline (2024)
Disability offers unique challenges concerning human rights conceptualisation and implementation, as persons with disabilities (PWDs) experience barriers and disadvantages in society not felt by their non-disabled peers. The Convention on the Rights of Persons with Disabilities (CRPD) fills the gaps left by pre-existing general human rights instruments, establishing a structure of disability-centric rights. However, the concept of disability is fluid and lacks a precise definition, making interpreting the Convention difficult. Methods to interpret and understand disability are still open for debate, generating academic discourse through the lens of disability models. These models generally fall under moral, medical, and social headings. Moral models perceive disability as a tragedy, relying on religious understandings of humanity. Medical models utilise pathology to generate a standardised biological classification of the human body, where disability becomes an ailment needing treatment. Social models emphasise disablement through barriers preventing available and equal access to society. Each model focuses on different aspects of the disability experience, and each carries strengths and weaknesses. This thesis argues that these weaknesses cause more problems than they solve. Instead, the disability rights discourse would benefit from a new perspective and model of disability. Identity provides this new perspective. By affording individuals the agency to dictate how and whether they identify with the term disability, the discourse surrounding human rights gains a new dimension. This thesis will use queer theory and crip theory as foundational bases to establish an identity approach. In highlighting how a queer identity contributes positively to the disability rights discussion, it will demonstrate how a postmodern and post-structural reading of the CRPD prioritises PWDs and ensures greater tangible access to human rights protections.